+0

# If square root 3 minus 1 is a root of the equation 2x^2 - 2kx + 4=0 then k equals

-1
82
1

If square root 3 minus 1 is a root of the equation 2x^2 - 2kx + 4=0 then k equals

Guest Nov 15, 2017

#1
+346
+2

ax+ bx + c = 0

To solve this problem, we need to use the formula X1*X2 = c ÷ a

(√3-1) * X= 4 ÷ 2

X= 2/ √3-1

Using that, we can figure out k,

Using this

X+ X= -a/b

(2/√3-1) + (√3-1) = -(-2k/2)

We got k = 2√3

Can someone check over my work? Not sure about the answer, pretty sure the solution is right...

supermanaccz  Nov 15, 2017
Sort:

#1
+346
+2

ax+ bx + c = 0

To solve this problem, we need to use the formula X1*X2 = c ÷ a

(√3-1) * X= 4 ÷ 2

X= 2/ √3-1

Using that, we can figure out k,

Using this

X+ X= -a/b

(2/√3-1) + (√3-1) = -(-2k/2)

We got k = 2√3

Can someone check over my work? Not sure about the answer, pretty sure the solution is right...

supermanaccz  Nov 15, 2017

### 12 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details